Endemic Covid-19: investigation at work from home among academic staff in Universiti Putra Malaysia from ergonomic perspective - Md Yusoff, Irwan Syah; Ab Samad, Aina Sufiah; Radzlan, Rohaizahtulamni (The Malaysian Consumer and Family Economics Association, 2023)
Multiple organizations and industries underwent significant changes due to theglobal coronavirus (COVID-19) outbreak in 2020. Everywhere, even in higher education institutions, it has caused harm to people, the economy, organizations, workers,and jobs, compelling companies to switch to a Work from Home (WFH) business model to maintain business continuity. This study utilizes an ergonomic principle to investigate work from home among university academic staff during the COVID-19 pandemic. The survey comprised a sample of 228 academic staff memberswho were selected through a simple random sampling technique. The data was collected by administering questionnaires and subsequently analyzed utilizing the Statistical Package for the Social Sciences (SPSS) software. The measurement of the independent and dependent variables was conducted using Pearson correlation. Based on the demographic characteristics of the participants in this survey, the results revealed that a significant proportion of the respondents (63.2) identified as female. Regarding age, most participants (108, or 47.4)were between the ages of 41 and 40. Additionally, a significant correlation was observed between the working environment and the productivity of academic staff at UPM (r =0.384). Consequently, the working environment emerges as the paramount determinant of productivity risk. The limited level of awareness regarding ergonomics education among Malaysian university academic staff may indicate the potential impact on their quality of life, working conditions, and overall health.